Pengendalian Asas Kebebasan Berkontrak Dalam Sistem Pre Project Selling - Irwan Gomulja; Habib Adjie (Universitas Muhammadiyah Surakarta, 2020)
Pre Project Selling is a sale before the project is built where the property being sold is just a picture or concept. This concept of marketing has become a trend in the modern era, especially for developers. The principle of freedom of contract in an agreement is a must-have foundation in the case of an agreement in a pre-project selling transaction. In consumer contracts made in standard written form prepared in advance by the developer. This means that all terms and conditions are made by the developer himself, so the consumer will only do so need to approve or reject the contract without the ability to change or add anything to PPJB content. The agreement generally does not consider enough the interests of other parties so that it is being questioned whether it still gives freedom to consumers. The absence of rules regarding Pre Project Selling in the applicable laws and regulations makes controlling consumer protection not optimal. The Government needs to make regulations on this matter.